The Concept Of Moral Character Formation According To Al-Ghazali And Its Implementation In Modern Education - Hanafi; Munawir; Abdul Haris; Benny Prasetiya (PT. Education Research Center, 2026)
This study analyzes Al-Ghazali's concept of moral formation and reconstructs its relevance for contemporary education. The background is the growing moral crisis in modern society, characterized by character degradation, value disorientation, weak self-control, and the dominance of materialistic and pragmatic orientations in educational practices. This study employs a qualitative approach with a library research design. Primary sources consist of Al-Ghazali's principal works Ihya' 'Ulum al-Din, Ayyuha al-Walad, and Mizan al-'Amal supplemented by scholarly books, journal articles, and studies on moral and Islamic education. Data were analyzed through content analysis and philosophical-hermeneutical interpretation. The findings reveal that moral formation, according to Al-Ghazali, is not merely external behavioral regulation but an internalized disposition embedded within the soul, from which virtuous actions emerge naturally and consistently. Moral education must therefore be cultivated through tazkiyat al-nafs, mujahadah, riyadhah, habituation of virtuous conduct, exemplary role modeling, and the integration of knowledge and action. Al-Ghazali's thought offers a humanistic-spiritual educational paradigm integrating intellectual, moral, emotional, and spiritual dimensions. In the context of modern education, this paradigm is highly relevant for strengthening character education, religious school culture, ethical digital behavior, and holistic student development. The study concludes that Al-Ghazali's moral educational philosophy provides a transformative conceptual foundation for reconstructing contemporary Islamic education amid the moral and spiritual challenges of the digital era.